Crack paths in smooth and precracked specimens subjected to multiaxial cyclic stressing - Nicholas R. Gates; Ali Fatemi (Fracture and Structural Integrity)
The understanding of shear-mode crack growth mechanisms and crack branching phenomena is of great interest for a variety of practical engineering situations. Despite this fact, relatively little research is available regarding these topics. Of the studies that have been performed, few provide a means of quantifying such effects and most consider crack growth starting from a precrack. The current study is aimed at trying to fill some of the research voids in these areas by investigating the effects of microcrack coalescence, loading level, and superimposed normal stresses on the mode II crack behavior of naturally initiated fatigue cracks. Based on the experimental results and subsequent analyses, it was determined that microcrack networks and coalescence have little to no effect on the experimentally observed crack paths regardless of the applied loading level. Instead, the preferred crack growth mode is shown to have a dependence on the applied shear stress magnitude and stress normal to the crack plane, indicating a significant role of fiction and roughness induced crack closure effects in the crack growth process. A simple model is then proposed to quantify these effects based on the idea that crack face interaction reduces the effective mode II SIF by allowing a portion of the nominally applied loading to be transferred through a crack. The model agrees qualitatively with the experimentally observed trends for pure torsion loading and predicts crack branching lengths within a factor of 2 for all loadings considered.